Structural Characterization of a Capillary Microfluidic Chip Using Microreflectance. Issue 6 (June 2017) - Lastras-Martínez, Luis F.; Balderas-Navarro, Raul E.; Castro-García, Ricardo; Hernández-Vidales, Karen; Almendarez-Rodríguez, Juan; Herrera-Jasso, Rafael; Prinz, Adrian; Bergmair, Iris
The structural characterization of capillary microfluidic chips is important for reliable applications. In particular, nondestructive diagnostic tools to assess geometrical dimensions and their correlations with control processes are of much importance, preferably if they are implemented in situ. Several techniques to accomplish this task have been reported; namely, optical coherence tomography (OCT) jointly with confocal fluorescence microscopy (CFM) to investigate internal features of lab-on-a-chip technologies. In this paper, we report on the use of a simple optical technique, based on near-normal incidence microreflectance, which allows mapping internal features of a microfluidic chip in a straightforward way. Our setup is based on a charge-coupled device camera that allows a lateral resolution of ∼2.5 µm and allows us to measure in the wavelength range of 640–750 nm. The technique takes advantage of the Fabry–Perot interferences features in the reflectance spectra, which are further analyzed by a discrete Fourier transform. In this way, the amplitude of the Fourier coefficients is modulated by the presence of a microfluidic channel.